European Policies for Short Sea Shipping and Intermodality - Psaraftis, Harilaos N.; Zis, Thalis (My University, 2019)
This chapter discusses European policies as regards short sea shipping (SSS) and intermodality. To that effect, a broad perspective is mainly taken, as recently there have been numerous policy initiatives in Europe that deal directly or indirectly with both sectors. The chapter takes stock at the situation as regards European ports and SSS and discusses challenges and prospects for the future. The analysis looks into both ports and SSS in a strict sense and other factors that are related, directly or indirectly, and that may have important ramifications. These other factors include EU port deregulation, the role of rail transport, environmental regulations, sulphur regulations, port security, and others. The chapter tries to explain the causes of current problems, investigates cross-linkages and makes suggestions for possible improvements.